SGLT2 inhibitors in lupus nephritis: a multicentric study in Latin America - José L. Daza; Gerardo Gutiérrez; Rosa L. Peñuela-Murcia; Andrés Cárdenas; Juan S. Reyes-Bello (Nefrología Latinoamericana)
Objective: The objective of the study is to examine the effect of sodium-glucose transporter 2 inhibitors (SGLT2) on proteinuria and renal function progression over 12 months in patients with proliferative lupus nephritis (LN). Material and methods: A retrospective observational analysis was conducted on patients with LN in Argentina and Colombia. Patients diagnosed with class III or IV + V LN were followed for 12 months. Out of 95 biopsies of focal or diffuse proliferative LN, 74 histological samples met the inclusion criteria. These were divided into two groups: Group A included 35 patients who received conventional treatment plus SGLT2 inhibitors (empagliflozin 10 mg daily) and Group B included 39 patients who received only conventional treatment. Both groups received the same dose of cyclophosphamide and maintenance with mycophenolic acid. Laboratory findings, proteinuria behavior, and renal function progression were evaluated over 12 months. Results: Among the 74 patients, 64 were women (86.4%), with a mean age of 34 ± 12 years. Group A showed a reduction in proteinuria at 12 months to 0.48 (0.38-0.71) compared to Group B, which did not receive SGLT2 inhibitors, with proteinuria at 0.8 (0.42-1.3) (p = 0.02). Conclusions: Patients who received conventional immunosuppressive treatment and added SGLT2 inhibitors showed a reduction in proteinuria over a 12-month follow-up period.